Electrospun Carbon Nanofiber Sprinkled with Co3O4 as an Efficient Electrocatalyst for Oxygen Reduction Reaction in Alkaline Medium. Issue 17 (7th May 2019) - Selvakumar, Karuppiah; Ulaganathan, Mani; Senthil Kumar, Sakkarapalayam Murugesan; Thangamuthu, Rangasamy; Periasamy, Padikkasu; Ragupathy, Pitchai
Abstract: Design and development of an efficient and earth abundant electrocatalyst for improving the kinetics of oxygen reduction reaction (ORR) is considered as important task especially in renewable energy sector and energy‐intensive appliances. In particular, developing a low cost, environmental benign, robust and stable ORR catalyst still remains a challenging task due to its sluggish kinetics. Here in this work we developed a simple and environmentally green electro‐spinning technique for decoration of cobalt oxides (Co3 O4 ) on polyacrylonitrile (PAN) fibers to generate a hybrid nanostructure of carbon nanofiber‐ Co3 O4 (CNF‐ Co3 O4 ) during calcinations and employed resultant electrocatalyst towards ORR. The CNF provided active surface to seed as well an anchoring spot for nanocrystals and act as a conducting network. The resulting CNF‐Co3 O4 hybrid displayed a supeior ORR current density that surpassed bare CNF and occurred via a 4 electron direct reduction pathway. It may due to the as formed heterogeneous interface during the decoration of Co3 O4 on CNF leads to enhanced conductivity and thereby decreases ORR overpotential as well as enhanced reaction rate at CNF‐Co3 O4 surface. Abstract : A simple and environmentally friendly electro‐spinning technique adopted for decoration of cobalt oxides (Co3 O4 ) on polyacrylonitrile (PAN) fibers to generate carbon nanofiber‐ Co3 O4 (CNF‐ Co3 O4 ). The resulting CNF‐Co3 O4 hybrid displayed a supeior ORR current density that surpassed bare CNF and occurred via a 4 electron direct pathway to water. It is believed that as formed heterogeneous interface in Co3 O4 on CNF leads to improved conductivity and thereby decreases ORR overpotential as well as enhanced reaction rate at CNF‐Co3 O4 surface.